A Locally Invasive Giant Cell Tumor of the Skull Base: Case Report - Billingsley, J. T.; Wiet, R. M.; Petruzzelli, G. J.; Byrne, R. (Journal of Neurological Surgery Reports, 2014)
Giant cell tumors (GCTs) are rare, usually affecting the epiphyses in long bones of the extremities. They seldom occur in the skull, where they preferentially affect the sphenoid and temporal bones. Considered to be benign, locally aggressive lesions, they may cause cranial nerve deficits by compression but infrequently invade the dura and parenchyma of the brain. Several case reports with follow-up describe gross total resection of skull base GCT to be curative. Anything short of total resection usually results in recurrence within 4 years. Radiation therapy, although controversial, is reserved for lesions that cannot be completely resected. Some argue, however, against the use of radiation because there are reported cases of malignant transformation. Here we describe the case of a large GCT that was invasive to the dura, temporal lobe, as well as the third division of the trigeminal nerve, and to date gross total resection has been curative of this lesion. The patient has not undergone radiation therapy.
Keywords: giant cell tumors; GCT; epiphyses; extremities; temporal bone; skull base tumor; radiotherapy